Revisionary notes on Bulbostylis (Cyperaceae) in India: new combinations, synonymy and lectotypification - Madhav, Nilesh Appaso; Bramhadande, Sneha Pradeep; Khot, Vasundhara Vilas; Dalavi, Jagdish Vishnu; Kambale, Sharad Suresh; Gosavi, Kumar Vinod C.; Chandore, Arun Nivrutti (Phytotaxa, 2026)
The present study provides taxonomic and nomenclatural clarifications within the genus Bulbostylis (Cyperaceae: Abildgaardieae) in India based on field surveys, herbarium studies, and detailed morphological examinations. Bulbostylis barbata subsp. pulchella is raised to species rank as Bulbostylis pulchella, while B. swamyi and B. maritima are reduced to synonyms of this species. The species previously known as Scirpus thwaitesii is transferred under the genus Bulbostylis, and its rediscovery after 188 years is reported. Lectotypes are designated for Isolepis pulchella and Scirpus thwaitesii to stabilize their nomenclature type. The study also provides descriptions, photoplates, nomenclatural notes, and a key to the Indian species of Bulbostylis.